Cheap Justice or Judicial Chaos? The Regulatory Crisis of AI Robot Lawyers in Indonesia - Syarifah Lisa Andriati; Inneke Kiki Rizki; Wan Nur Addibah Binti Adnan (Universitas Negeri Semarang, 2026)
Artificial intelligence (AI) technology is advancing rapidly, and it has a significant impact on various disciplines, including the legal profession. In the United States, AI has already been given a role in legal representation wherein the AI model known as the Robot Lawyer, handled cases regarding two traffic violations 2023. From thereon, it has become critical to examine the extent of AI Robot Lawyer’s role in the digital legal revolution, as well as the related opportunities and challenges within the Indonesian legal system. This study uses a normative legal research method based on a literature review. Our results show that defendants can use Robot Lawyers as legal advisors by utilizing the ‘DoNotPay’ app to listen to arguments before the court, in real time and then be informed on what to say through earphones. The positive impacts of using Robot Lawyers include, among others, the convenience of defendants when facing legal charges and the cost factor which is relatively low. However, judges should be cautious when using AI in court because parties without human legal representation are unlikely to be able to aptly comprehend the arguments and claims made by a Robot Lawyer. In Indonesia, AI can support legal problem-solving but cannot replace lawyers in court. If Robot Lawyers are to be implemented, a strong legal foundation is needed. The regulations of the related court procedures must be reformed and clear guidelines must be provided to safeguard the rights and interest of the defendants who are relying on Robot Lawyers.